Effectiveness of different extrinsic feedback forms on motor learning in children with cerebral palsy: a systematic review. Issue 8 (10th April 2023) - Schoenmaker, Jorine; Houdijk, Han; Steenbergen, Bert; Reinders-Messelink, Heleen A.; Schoemaker, Marina M.
Abstract: Purpose: Motor learning interventions for children with cerebral palsy (CP) that elicit relatively permanent and transferable improvements in motor skill capability are essential. Knowledge is needed about the augmented feedback forms that most effectively promote this. This review aims to collect and analyze the current evidence for the effectiveness of different forms of feedback for motor learning in children with CP to improve motor task performance. Methods: PubMed, PsycInfo, and Cochrane Library were searched to identify relevant studies. Studies were included if (1) they were conducted in children with CP or compared children with CP to TD children and (2) a form of augmented feedback related to a motor task was administered. Results: Initially, 401 records were identified for screening. Ultimately, 12 articles were included in the review. The evidence thus far supports the expectancy that children with CP generally benefit from feedback provided during or after performing a movement task. Conclusion: Due to the heterogeneity of existing studies, it is difficult to draw firm conclusions regarding relative effectiveness of feedback forms. This review showed that more high-quality research is warranted on the effectiveness of specific feedback forms on motor learning in children with CP. Implications for Rehabilitation: Children with CP benefit from several forms of knowledge of performance or knowledge of results feedback provided during or after performing a movement task. Feedback should not be provided with every performed trial. Feedback frequency can best be reduced by letting children determine after which trials they want feedback. Learning curves under similar feedback conditions varied largely between children, warranting tailor-made forms of feedback to be applied during motor learning and rehabilitation.